Supervision of Elderly Cadres in Education on Handling Bloating with Hot Compress on the Abdominal Area - Rustam Aji Rochmat; Dewi Lusiani; Sherly Ratih Frichesyarius Santi Ajhie; Roro Ajhie Ayuningtyas; Kusmiyati; Yani Sriyani (CV. Get Press Indonesia, 2025)
Background: Acute abdominal pain is an emergency that can occur due to surgical and non-surgical problems. Patients with acute abdomen come with complaints of abdominal pain that occurs suddenly. Handling of bloating with hot compresses in the abdominal area, One of the first aid that is easily available in families and communities.Objective: hot compresses in the abdominal area, or stomach, can help relieve pain and bloating. Community service method: Assisting elderly cadres in first aid with hot compresses in the abdominal area r. Activity Results: Counseling attended by 6 elderly cadres and 21 elderly, given material on handling bloating with hot compresses in the abdominal area. Discussion: Hot compresses in the abdominal area are hot compresses in the abdominal area, or stomach, can help relieve pain and bloating. The heat from the compress can dilate blood vessels, improve circulation, and make muscles more relaxed, thereby reducing pain and discomfort. Conclusion: Participants 2 out of 6 elderly cadres and 4 out of 21 elderly were able to redemonstrate how to treat bloating with a hot compress on the abdomen. Suggestion: The community can provide first aid for treating bloating with a hot compress on the abdomen.